Nonalcoholic fatty liver disease - Brunt, Elizabeth M. (2015)
Nonalcoholic fatty liver disease (NAFLD) is a disorder characterized by excess accumulation of fat in hepatocytes (nonalcoholic fatty liver (NAFL)); in up to 40% of individuals, there are additional findings of portal and lobular inflammation and hepatocyte injury (which characterize nonalcoholic steatohepatitis (NASH)). A subset of patients will develop progressive fibrosis, which can progress to cirrhosis. Hepatocellular carcinoma and cardiovascular complications are life-threatening co-morbidities of both NAFL and NASH. NAFLD is closely associated with insulin resistance; obesity and metabolic syndrome are common underlying factors. As a consequence, the prevalence of NAFLD is estimated to be 10–40% in adults worldwide, and it is the most common liver disease in children and adolescents in developed countries. Mechanistic insights into fat accumulation, subsequent hepatocyte injury, the role of the immune system and fibrosis as well as the role of the gut microbiota are unfolding. Furthermore, genetic and epigenetic factors might explain the considerable interindividual variation in disease phenotype, severity and progression. To date, no effective medical interventions exist that completely reverse the disease other than lifestyle changes, dietary alterations and, possibly, bariatric surgery. However, several strategies that target pathophysiological processes such as an oversupply of fatty acids to the liver, cell injury and inflammation are currently under investigation. Diagnosis of NAFLD can be established by imaging, but detection of the lesions of NASH still depend on the gold-standard but invasive liver biopsy. Several non-invasive strategies are being evaluated to replace or complement biopsies, especially for follow-up monitoring.